Enhancing Students Descriptive Essay Writing Skills Using Think Talk Write Model With Image Media - Nur Syafika, Mifta; Endah Sugiharti, Rini; Victorynie, Irnie (Elementary Teacher Education Program, Majalengka University, 2024)
This study is motivated by the low ability of students in writing descriptive essays in Indonesian language learning, which is caused by the use of monotonous lecture methods and the lack of use of interesting learning media. This causes students to have difficulty determining the right title, generating relevant ideas, composing cohesive and coherent paragraphs, and using punctuation correctly. This study aims to improve the writing skills of fifth grade students of public elementary school Pondok Kopi 08 Pagi through the application of the Think Talk Write (TTW) model with the help of picture media. The research was conducted using the Classroom Action Research (PTK) approach which was carried out in two cycles. Each cycle included planning, action implementation, observation, and reflection stages. The research subjects consisted of 26 fifth grade students of public elementary school Pondok Kopi 08 Pagi, consisting of 12 male students and 14 female students. Data were obtained through writing tests, observation sheets, and documentation, then analysed by comparing the average of the initial, cycle I, and cycle II scores. The results showed a significant improvement in students' writing ability. The average score increased from 65.7 in cycle I to 84.3 in cycle II. The level of learning completeness also increased from only 3 students (7.69%) in the initial condition to 22 students (84.61%) in cycle II. Thus, the TTW model assisted by picture media proved effective in improving description essay writing skills. The researcher recommends the consistent use of this model in Indonesian language learning to improve students' learning outcomes.